How to overcome the cost of a criminal record for getting hired - Rennó Santos, Mateus (Criminology, 2023)
Many theories emphasize how employment is protective against criminal recidivism, yet a criminal record is a major barrier for getting hired. We asked 591 managers to make hypothetical hiring decisions between two applicants whose key difference was the presence or absence of a criminal conviction. In addition, we randomly manipulated the education, references, wage, or experience of the applicant with the criminal record to identify which manipulations can offset the cost of the record on an applicant's probability of being selected. We found that, when credentials were the same, the applicant with a criminal record was unlikely to be hired. That applicant, however, could become likely to be hired (i.e., the likelihood crossed 50 percent) by having at least 1 year of relevant experience, a GED or a college degree, or references from a former employer or a professor. Incomplete degrees, references from criminal justice professionals, or wage discounts did not make the applicant with the record likely to be hired. Findings confirm that a criminal record carries a high employability cost but also indicate that this cost can be superseded by specific credentials that signal an applicant's reliability, which can be provided by existing programs and institutions.